2023
DOI: 10.1109/access.2023.3235896
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Optimization of Antennas for Structural Health Monitoring

Abstract: Monitoring and surveillance of buildings, especially in critical infrastructure is crucial to increase the lifetime of such structures. This is due to fact, that buildings from reinforced concrete, like bridges or road tunnels are prone to corrosion due to their exposition to the elements. For this task, wireless sensor nodes can be employed in structural health monitoring. In the last few years passive RFID sensors have been proposed to gather data from inside concrete structures. However, designing antennas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Moreover, it was found that, presence of bitch of steel bars within the concrete has effect on wireless communication, with the effect varying with the width of the bars [58]. An optimized antenna embedded in concrete for SHM was designed and tested in [59]. The antenna operates in UHF and was tested over a wide range of electrical properties and achieved a reflection coefficient of -13dB, and a gain of -8.4dBi, at concrete water content of 4.2%.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, it was found that, presence of bitch of steel bars within the concrete has effect on wireless communication, with the effect varying with the width of the bars [58]. An optimized antenna embedded in concrete for SHM was designed and tested in [59]. The antenna operates in UHF and was tested over a wide range of electrical properties and achieved a reflection coefficient of -13dB, and a gain of -8.4dBi, at concrete water content of 4.2%.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to the difficulty of installing sensors in the field [142], many sensors used in construction, such as load cells, strain gauges, and accelerometers, are susceptible to non-linear response and hysteresis [143]. Sensors embedded in structures or used in geotechnical applications are sensitive to mechanical stress, which can degrade their performance or cause failure over time [144].…”
Section: The Challengesmentioning
confidence: 99%
“…Previous work by the authors of this publication, focused on the design of RFID‐antennas with small dimensions [16], or on the optimisation of antennas embedded in material with varying electrical properties [27].…”
Section: Introductionmentioning
confidence: 99%